Effects of urban form on air quality in China: An analysis based on the spatial autoregressive model. (June 2019) - Li, Fan; Zhou, Tao
Abstract: Understanding how urban air quality depends on urban form can have important implications for improving urban air quality by optimizing urban planning and management policies. This study employed the spatial autoregressive model to explore the effect of urban form on urban air quality in 288 prefecture-level cities in China. Information on the air quality (AQI) and six criteria pollutants (PM2.5, PM10, CO, SO2, NO2, O3 ) were obtained from the hourly observation data of 1333 in-situ air monitoring stations throughout 2015. Urban form is characterized by five metrics, including urban size, shape, sprawl, fragmentation and traffic accessibility, and it is calculated based on land cover data. Results show that urban shape complexity and population density have a significant negative impact on urban air quality. Large city size is strongly related to comparatively poor air quality for cities in Southern China and only shows a slight association with emissions in Northern China. In general, lower-sized, scattered, polycentric cities provide better air quality in China. It is suggested that higher air quality and fewer pollutant emissions can be achieved through urban form planning and management policies, which aim to restrict the blind expansion of urban land and encourage moderately scattered, polycentric urban development. Highlights: Single shaped and densely populated cities are related to worse air quality in China. City size has a strong negative effect on air quality in southern China but a slight impact on emissions in northern China. In general, lower-sized, scattered, polycentric urban forms are generally associated with better air quality in China.